The Relationship Between Clean Water Sources And The Incidence Of Diarrhea In Kampung Baru Resident At Ngagelrejo Wonokromo Surabaya - I Made Subhawa Harsa (Journal of Agromedicine and Medical Sciences, 2019)
Abstract Water is a good medium for bacterial growth, so that contamination is happening especially if less attention in terms of hygiene and sanitation. The use of bed water sources can increase the risk of diarrhea. Diarrhea is one of the environmentally based disease is a major cause of morbidity and mortality. Kampung Baru village located around Jagir Kali Surabaya Most people are in the middle to low socioeconomic level. The lifestyle of them, also pays less attention to environmental hygiene and sanitation, so that it can cause water pollution which can increase the risk of diarrhea. This study was an observational analytic cross sectional study. Entire study population villagers of Kampung Baru. A sample of 75 respondents drawn with simple random sampling technique. The data used is primary data obtained through the distribution of questionnaires, interviews, and observations. Data analysis using the Spearman rank test with a significance level (α = 0.1). The results showed that 53,3% affected diarrhea and 46,7% didn’t affected (P =0.087, r=0.463). The results showed a medium correlation between the source of water with the incidence of diarrhea in Kampung Baru Resident At Ngagelrejo Wonokromo Surabaya. Keyword : Diarrhae, Water Sanitation